Quantum Confinement in Aligned Zigzag "Pseudo‐Ribbons" Embedded in Graphene on Ni(100). (25th November 2021) - Sala, Alessandro; Zou, Zhiyu; Carnevali, Virginia; Panighel, Mirco; Genuzio, Francesca; Menteş, Tevfik O.; Locatelli, Andrea; Cepek, Cinzia; Peressi, Maria; Comelli, Giovanni; Africh, Cristina
Abstract: Lateral quantum confinement is of great interest in tuning the electronic properties of graphene‐based nanostructures, making them suitable for technological applications. In principle, these properties might be controlled through the edge topology: for example, zigzag nanoribbons are predicted to have spin‐polarized edge states. The practical realization of these structures is of utmost importance in fully harnessing the electronic properties of graphene. Here, the formation of regular, 1.4 nm wide ribbon‐like graphene structures with zigzag edges are reported, showing 1D electronic states. It is found that these "pseudo‐ribbons" embedded in single‐layer graphene supported on Ni(100) can spontaneously form upon carbon segregation underneath 1D graphene moiré domains, extending hundreds of nanometers in length. On the basis of both microscopy/spectroscopy/diffraction experiments and theoretical simulations, it is shown that these structures, even though seamlessly incorporated in a matrix of strongly interacting graphene, exhibit electronic properties closely resembling those of zigzag nanoribbons. Abstract : Regular, 1.4 nm wide "pseudo‐ribbons" with zigzag edges, embedded in single‐layer graphene supported on Ni(100), demonstrate that 1D properties induced by lateral quantum confinement of electrons can be obtained without creating physical edges (as in the case of nanoribbons), i.e., while preserving the integrity of targeted 2D materials.